G202(P) From amazon prime to theatre prime: the last mile delivery. (May 2019) - Verma, A; Thakkar, D; Fox, G; Milan, A
Abstract : Background: The last mile delivery model is a well-known corporate concept that has been adopted by successful businesses such as Amazon. It comprises of systematic optimisation of multiple steps of a complex delivery process, aiming for timely deliveries and improved customer care experience. Similarly, Neonatal Units (NNUs) with surgical provisions face logistical challenges when moving patients from NNU to a surgical theatre. Surgical time is expensive; costing around £1200 per hour 1 . Unlike the well-established Amazon model, the process of moving these babies has never been mapped systematically. Aim: Step-wise mapping of baby journeys to theatre, highlighting possible inefficiencies and providing benchmarking of current standards. Methods: Prospective anonymized data collection of all consecutive NNU to theatre transfers within a 4 month period, documentation of time spent in each step and data analysis using Microsoft Excel. Results: 25 baby journeys were mapped. Each journey included 6 steps: baby moved to transport incubator, journey to theatre, transfer to surgical table, surgical time, back to transport incubator, return to NNU. Porters facilitated both transfers. Initial estimated surgery start time was often postponed (64%>90 min). Babies were ready in incubator within 15 min of updated requested time (52%). However, 50% of the patients waited >20 min in transport incubators for porters to arrive. Once called to retrieve the patient post-op, the NNU team took an average of 14 min to reach theatre. They remained in theatre for >20 min in 56% of cases, as the patient was not ready to be moved (32%) or the porters were not available (23%). Conclusions: The last mile delivery of a baby to theatre is a complex multistep process that requires a multidisciplinary effort. Our findings have been presented to key stakeholders (neonatologists, surgeons, anaesthetists, theatre staff) proving the need for a strategic platform to develop a more systematic approach to this complex process. The strategy required would need to mimic similar user experience offered by successful delivery providers like Amazon. Reference: Fletcher D, et al. Improving theatre turnaround time. BMJ Open Quality 2017.